Bluefin Larvae in Oligotrophic Ocean Foodwebs, investigations of nutrients to zooplankton: overview of the BLOOFINZ-Gulf of Mexico program. (16th July 2022) - Gerard, Trika; Lamkin, John T; Kelly, Thomas B; Knapp, Angela N; Laiz-Carrión, RaÚl; Malca, Estrella; Selph, Karen E; Shiroza, Akihiro; Shropshire, Taylor A; Stukel, Michael R; Swalethorp, Rasmus; Yingling, Natalia; et al.
Abstract: Western Atlantic bluefin tuna (ABT) undertake long-distance migrations from rich feeding grounds in the North Atlantic to spawn in oligotrophic waters of the Gulf of Mexico (GoM). Stock recruitment is strongly affected by interannual variability in the physical features associated with ABT larvae, but the nutrient sources and food-web structure of preferred habitat, the edges of anticyclonic loop eddies, are unknown. Here, we describe the goals, physical context, design and major findings of an end-to-end process study conducted during peak ABT spawning in May 2017 and 2018. Mesoscale features in the oceanic GoM were surveyed for larvae, and five multi-day Lagrangian experiments measured hydrography and nutrients; plankton biomass and composition from bacteria to zooplankton and fish larvae; phytoplankton nutrient uptake, productivity and taxon-specific growth rates; micro- and mesozooplankton grazing; particle export; and ABT larval feeding and growth rates. We provide a general introduction to the BLOOFINZ-GoM project (Bluefin tuna Larvae in Oligotrophic Ocean Foodwebs, Investigation of Nitrogen to Zooplankton) and highlight the finding, based on backtracking of experimental waters to their positions weeks earlier, that lateral transport from the continental slope region may be more of a key determinant of available habitat utilized by larvae than eddy edges per se.